A surgical drill guide for pedicle screw placement - Kashani, Jamal (2012)
Despite efficiency of modern techniques and facilities, unplanned perforation and drill deviation could be happened during freehand drilling. The aim of this study was to provide a methodology for fabricating surgical drill guide for spinal surgeries. The data of patient obtained from computed tomography. Image processing and three dimensional modeling software packages were utilized in order to carry out screw insertion and design surgical guide. Rapid prototyping technique was used to manufacture the surgical guide. This technique provides the ability of fabricating surgical drill guide with proper fitting on vertebra while it was flexible in term of changing drill diameter.